Awareness and knowledge of disease surveillance and notification by health-care workers and availability of facility records in Anambra state, Nigeria - Nnebue, Chinomnso C. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Disease surveillance and notification (DSN) is part of the Health Management Information System (HMIS) which comprises databases, personnel, and materials that are organized to collect data which are utilized for informed decision making. The knowledge about DSN is very important for the reporting of notifiable diseases. OBJECTIVE: The aim of this study is to examine the awareness and knowledge of health-care workers about DSN, and availability of facility records in Anambra State, Nigeria. MATERIALS AND METHODS: The study was a descriptive cross-sectional one in which relevant data were collected from health-care workers selected by a multistage sampling technique. Qualitative information was also elicited by key informant interviews, whereas an observational checklist, preceded by a desk review was used to examine the availability of facility records. RESULTS: Although 89.8% of the health-care workers were aware of the DSN system, only 33.3, 31.1, and 33.7% of them knew the specific uses of forms IDSR 001, IDSR 002, and IDSR 003 (IDSR: Integrated Diseases Surveillance and Response), respectively. Knowledge of use of the various forms at the facility and local government area (LGA) levels were generally low, although the observational checklist revealed that IDSR 001 and IDSR 002 forms were predominantly found in primary health-care facilities. HMIS forms were less likely to be available in secondary health-care facilities (χ(2)=7.67, P=0.005). CONCLUSIONS: Regular training and retraining of concerned health-care workers on DSN at the LGA level is recommended. This should run concurrently with adequate and regular provision of IDSR forms, copies of the standard case definitions, and other necessary logistics to the health-care facilities by the local and state governments.